MC Azure data fundamentals guide study guide Exam DP-900 - Switzer, Jake (WILEY-SYBEX, 2022)
The most authoritative and complete study guide for people beginning to work with data in the Azure clo.ud In MC Azure Data Fundamentals Study Guide: Exam DP-900, expert Cloud Solution Architect Jake Switzer delivers a hands-on blueprint to acing the DP-900 Azure data certification. The book prepares you for the test - and for a new career in Azure data analytics, architecture, science, and more - with a laser-focus on the job roles and responsibilities of Azure data professionals. You'll receive a foundational knowledge of core data concepts, like relational and non-relational data and transactional and analytical data workloads, while diving deep into every competency covered on the DP-900 exam. You'll also get: Access to complimentary online study tools, including hundreds of practice exam questions, electronic flashcards, and a searchable glossary Additional prep assistance with access to Sybex's superior interactive online learning environment and test bank Walkthroughs of skills and knowledge that are absolutely necessary for current and aspiring Azure data pros in introductory roles Perfect for anyone just beginning to work with data in the cloud, MC Azure Data Fundamentals Study Guide: Exam DP-900 is a can't-miss resource for anyone prepping for the DP-900 exam or considering a new career working with Azure data.